Knowledge, Awareness, and Practice of Safety and Emergency Response Among Scuba Divers in Malaysia: Questionnaire Development and Validation - Aladin, Muhammad; Wan Mohd Zahiruddin, Wan Mohammad; Siti Rabiatull Aisha, Idris; Ahmad Filza, Ismail (Springer Nature, 2024)
Introduction: Safety has become paramount to ensure that scuba diving continues to expand into new markets, with minimal risks, and that scuba diving translates into a safe and relaxed adventure in response to growing market demands. Research focusing on assessing the knowledge, awareness, and practices (KAP) regarding safety and emergency response among scuba divers has been limited, and there is a need for validated assessment tools in this area.